2004
DOI: 10.1002/bmc.362
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion electrokinetic chromatography with laser‐induced fluorescence detection: as tested with amino acid derivatives

Abstract: Over a decade ago, microemulsion electrokinetic chromatography was introduced as a novel mode of capillary electrophoresis. However, there has not been publication on the combination of microemulsion electrokinetic chromatography with laser-induced fluorescence detection. In this paper, a preliminary method using microemulsion eletrokinetic chromatography combined with laser-induced fluorescence detection and second derivative electrophoregram was established as a sensitive and selective assay for separation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Increasing the buffer concentration of the electrolyte has been shown to improve peak resolution [20,45]. Using a low concentration of borate buffer in the microemulsion gave a faster separation because of the faster EOF at low ionic strengths, but the precision of subsequent injections was lower due to electrolysis effects [28].…”
Section: Buffer Type and Concentrationmentioning
confidence: 98%
See 1 more Smart Citation
“…Increasing the buffer concentration of the electrolyte has been shown to improve peak resolution [20,45]. Using a low concentration of borate buffer in the microemulsion gave a faster separation because of the faster EOF at low ionic strengths, but the precision of subsequent injections was lower due to electrolysis effects [28].…”
Section: Buffer Type and Concentrationmentioning
confidence: 98%
“…MEEKC methods have been used to perform quantitative determinations including UV filters in sunscreen lotions [41], preservatives in pharmaceutical and cosmetic products [10], catechins in green tea [27], pharmaceuticals [9,19,51,62] and biphenyl nitrile compounds [6]. Using MEEKC coupled with laserinduced fluorescence detection offers more sensitivity for quantitative methods of determining amino acid derivatives [45] and ephedrine and pseudoephedrine [63]. Table 1 shows some quantitative results obtained from various MEEKC methods.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Melin and Perret [73] compared the analysis of UV absorbing compounds in human urine by MEKC and MEEKC but found that MEEKC offered no advantages for routine analysis. The use of MEEKC for the analysis of amino acid derivatives resulted in poor reproducibility and long analysis time [54]. However, the use of a novel double coating of a combination of a removable covalent layer and an SDS layer on the capillary resulted in [54] faster and more reproducible Table 4 lists recent bioanalytical applications of MEEKC.…”
Section: Bioanalysismentioning
confidence: 99%
“…Increasing the buffer concentration in the aqueous phase of the microemulsion electrolyte has been shown to improve peak resolution [22,54]. High buffer concentrations suppress the EOF and generate high currents, which may limit the level of voltage that can be applied.…”
Section: Buffer Concentration and Additivesmentioning
confidence: 99%
See 1 more Smart Citation